If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 20 + 3(2) Multiply 3 * 2 y = 20 + 6 Combine like terms: 20 + 6 = 26 y = 26 Solving y = 26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 26
| 2x-5+5y=-5x+16 | | t^2+3t+3=5 | | 7k-14=40 | | y=20+3(1) | | (c+d)+y= | | (x/5)+3=(1/3) | | 22/20=99/x | | .15-.2x=.3(x-3) | | (x+2k)(x-3k)=x^2+2x-24 | | n^3=16n | | y=20+3(0) | | (7+u)(3u+2)=0 | | 9f-25=96 | | 3(v-5)=5(v-4) | | -6x+(2a+5)= | | -21x+3=-39 | | .15-.2=.3(x-3) | | 21=140+4c | | 8(172.25)+3b=152.50 | | 22/18=x/27 | | y/3-2=5 | | X^2-8x-15=-6 | | 1.4m=16.8 | | y^3=ay | | -5+2=13 | | m/-15=0 | | 4=p+9 | | 16X-3(3+2x)=6x+2 | | 55=-5x | | (6x-7)(30x^2+12x+45)= | | 40d+.25m=25d+.45m | | 3.2-4d=3.2d+3 |